PROGRAM DESA BERDERING DI "DESA KARAMPUANG" KABUPATEN MAMUJU - Eko, Bambang Riawan (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
This reseach seeks to answer the emering issue of what are factor led to the failure of Program Desa Berdering at Karampuang Village, Mamuju District. This evaluative study attempts to describe the contributing factors of the failure of the program at the village. According, there are 3 sources in this study, i.e. Head ofKarampuang village, villagers whose land are occupied by public telepohone infrastructure as well as the Rhead of Communication and Technology Office ofDepartement of Transportation, Communication and Information Technology Office ofMamuju Regency. It can be concluded from the results that there are lack of coordination among Rural Telecommunications and Information Technology Center, local government and managing partners led to the emergence of problems. The low participation ofKarampyang village toward this project was due to the fact that the public expectation did not conform with the provision of the government, therefore the people werw being apathetic in addressing the issue. In addition, the technology provided by the government are not as good as the current one used by Karampuang villagers.